Community Behavior Study Regarding Drug Purchases at Bengkulu City Pharmacies in 2021 - Avrilya Iqoranny Susilo; Zamharira Muslim (Politeknik Kesehatan Kemenkes Jakarta II, 2022)
At this time the practice of self-medication or self-medication is increasingly being carried out by the community. This is done for various reasons, including feeling that the disease they are suffering from is only a minor illness that does not need to be treated by a doctor. This study aims to get a picture of people's behavior when searching for drugs at pharmacies in their self-medication practice in the Bengkulu City area. The research was conducted using a direct survey research method using observation sheets. Determination of the sample of pharmacies and respondents was done by using purposive sampling technique. People already have a choice of what medicine they will buy at the pharmacy to relieve the pain they feel (84.7%) and ask pharmacists for advice in making choices (15.3%). Most of the drugs used in the practice of self-medication by the community are brand-name drugs (81%) and a small percentage of people use generic drugs (19%). The choices in the use of drugs are over-the-counter drugs (21.4%), limited over-the-counter drugs (28.8%) and hard drugs (49.8%). Based on this, the behavior of people who go to pharmacies to practice self-medication, most of them already have a choice of what medicine they will buy to relieve the pain they feel. The thing that must be a concern is that many people choose to use hard drugs in their self-medication practice without asking for advice from pharmacists at the pharmacy (49.8%), while hard drugs in their use must use a doctor's prescription.